2011
DOI: 10.1097/adm.0b013e3182034e31
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Use of Buprenorphine/Naloxone Among Injecting and Noninjecting Opioid Users

Abstract: Objectives We examined the use, procurement, and motivations for the use of diverted buprenorphine/naloxone among injecting and noninjecting opioid users in an urban area. Methods A survey was self-administered among 51 injecting opioid users and 49 noninjecting opioid users in Providence, RI. Participants were recruited from a fixed-site syringe exchange program and a community outreach site between August and November 2009. Results A majority (76%) of participants reported having obtained buprenorphine/n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
91
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 24 publications
11
91
1
Order By: Relevance
“…The development and implementation of new products to offer treatment for opioid dependence while minimising risks of patient noncompliance and illicit diversion have been used (White et al, 2009). Early phase I trial evidence would suggest extremely positive results, claiming it holds withdrawal symptoms and controls craving with no reported safety issues (Bazazi et al, 2011). A phase II trial of a buprenorphine depot monthly injection is also currently ongoing (Reckitt Benckiser Pharmaceuticals, Inc., 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The development and implementation of new products to offer treatment for opioid dependence while minimising risks of patient noncompliance and illicit diversion have been used (White et al, 2009). Early phase I trial evidence would suggest extremely positive results, claiming it holds withdrawal symptoms and controls craving with no reported safety issues (Bazazi et al, 2011). A phase II trial of a buprenorphine depot monthly injection is also currently ongoing (Reckitt Benckiser Pharmaceuticals, Inc., 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has reported a wide range of estimates for illicit OSD use among IDUs. Estimates of illicit buprenorphine use range from 9% to 41% in US samples (Bazazi et al, 2011;Genberg et al, 2013), to 73% reported in a Finnish sample (where buprenorphine is the most commonly used illegal opiate) (Alho et al, 2007). In terms of illicit methadone use, a US-based study reported a 16% rate of street methadone use over the last six months (Mitchell et al, 2009), while an Australian study reported a decline in recent methadone injecting from 31% to 13% during the relatively short time period (1997)(1998)(1999)(2000) (Darke et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly diverted to relieve opioid withdrawal symptoms and to reduce the use of other opioids. 7 Patients report using it when they are out of money or opioids. Buprenorphine can be used in doses higher than the daily maintenance dose to provide intermittent euphoria and intoxication.…”
Section: W E Congratulate Mayo Clinic Proceedings and The Authors Hammentioning
confidence: 99%